Can Fur Traders Have Feelings? Sentiment in Samuel Hearne’s Journey to the Northern Ocean (1795) - Greenfield, Bruce (Studies in Canadian Literature / Études en littérature canadienne, 2012)
Samuel Hearne’s lurid and sentimental recounting of the “Bloody Falls” massacre in Journey to the Northern Ocean (1795) has raised doubts as to whether the fur trader was, in fact, the account’s author. However, historical documents indicate that Hearne was capable of writing at the level of complexity and correctness seen in this passage: Hearne’s letters to the London directors of the HBC significantly differ stylistically from his post journals; Hearne’s family, education, and interests are consistent with those of an aspiring writer; and most importantly, the account of the massacre is consistent with ideas, analogous incidents, emotional expressions, and the narrating persona found throughout the Journey, all of which suggest Hearne’s familiarity and engagement with the influential sentimentalist thought of his time.